2016
DOI: 10.1002/cpp.2063
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Differences Between Suicide Ideators and Suicide Attempters in Patients with Mental Disorders

Abstract: Recent suicide attempters show higher levels of hopelessness, borderline symptoms and NSSI than lifetime attempters and suicide ideators. Clinicians should focus attention on assessing hopelessness, borderline symptoms and NSSI in those with suicide ideation. Lower levels of meaning in life are related to recent suicide attempts. Levels of hopelessness differentiate between recent and lifetime suicide attempters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
(104 reference statements)
2
10
1
Order By: Relevance
“…Finally, non‐ideators/attempters showed lower levels of lifetime frequency of NSSI, number of NSSI methods, number of intrapersonal and interpersonal NSSI functions, suicide ideation, hopelessness, and borderline symptoms, compared to ideators and attempters, in agreement with previous research (Pérez et al., ). However, we did not find differences in hopelessness, suicide ideation, borderline symptoms, or lifetime frequency of NSSI between ideators and attempters.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Finally, non‐ideators/attempters showed lower levels of lifetime frequency of NSSI, number of NSSI methods, number of intrapersonal and interpersonal NSSI functions, suicide ideation, hopelessness, and borderline symptoms, compared to ideators and attempters, in agreement with previous research (Pérez et al., ). However, we did not find differences in hopelessness, suicide ideation, borderline symptoms, or lifetime frequency of NSSI between ideators and attempters.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, cutting has been associated with an increased probability of suicide (Andover, Pepper, Ryabchenko, Orrico, & Gibb, ; Dougherty et al., ; Victor & Klonsky, ). Finally, different studies have found borderline symptoms associated to suicide attempts (Oldham, ; Paris & Zweig‐Frank, ; Pérez et al., ).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 3 more Smart Citations